2010
DOI: 10.1889/jsid18.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Instability dependent upon bias and temperature stress in amorphous‐indium gallium zinc oxide (a‐IGZO) thin‐film transistors

Abstract: Abstract— The effects of gate‐bias stress, drain‐bias stress, and temperature on the electrical parameters of amorphous‐indium gallium zinc oxide (a‐IGZO) thin‐film transistors have been investigated. Results demonstrate that the devices suffer from threshold‐voltage instabilities that are recovered at room temperature without any treatments. It is suggested that these instabilities result from the bias field and temperature‐assisted charging and discharging phenomenon of preexisting traps at the near‐interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Figure 9 shows the time dependence of the Vth shift (∆Vt) for conventional coplanar IGZO TFTs and the proposed FCPL/BCPL IGZO TFTs under gate-bias temperature stress. The Vth shift data caused by charge trapping mechanism can be fitted by the stretched exponential dependence model as shown below [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 shows the time dependence of the Vth shift (∆Vt) for conventional coplanar IGZO TFTs and the proposed FCPL/BCPL IGZO TFTs under gate-bias temperature stress. The Vth shift data caused by charge trapping mechanism can be fitted by the stretched exponential dependence model as shown below [5].…”
Section: Resultsmentioning
confidence: 99%
“…The one of critical factors of IGZO TFTs in applications and mass production is the reliability-the threshold voltage (Vth) stability, which is affected by interface charge trapping between IGZO and gate insulator (GI) [5]. It was found that the optimizing GI surface showed the less hysteresis window than the un-optimizing GI surface, and the optimizing GI surface decreased the Vth shift under gate-bias stress [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is important to note that the performance stability of metal oxide TFTs is not only an issue on solution-processed devices, but also one that is observed in vacuumprocessed TFTs. For this reason, there is an ample body of research on the effects of mechanical bending, humidity, light, gate bias stress or temperature on the stability of these devices [31,104,105]. This is necessary in order to understand the degradation mechanisms of flexible TFTs and improve the robustness of the resulting circuits and systems.…”
Section: Flexible Metal Oxide Tftsmentioning
confidence: 99%